International Pricing of Emerging Market Corporate Debt : Does the Corporate Matter? - Keller, Sonja; Mody, Ashoka (Washington, D.C. : International Monetary Fund, 2010)
We examine risk spreads charged on corporate bonds placed by emerging market borrowers on international exchanges. While global developments have an important effect on spreads, changes in firm-level default risk also matter significantly in a way consistent with theory and experience in mature markets. In contrast, except during periods of financial crisis, country factors play a limited role. These findings go against the supposition that limited information on emerging market firms or significant agency problems prevent firm-level credit discrimination by international investors. The firm-level information capitalization into spreads possibly reflects protection afforded by the exchange listing on international markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet